ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KESIAPAN USAHA MIKRO BERBASIS AGRIBISNIS DI KOTA BENGKULU TERHADAP PENGGUNAAN ALAT PEMBAYARAN QUICK RESPONSE INDONESIAN STANDARD - Ridha Rizki Novanda; Zamdial Zamdial; Musriyadi Nabiu; Dede Hartono; Ari Anggoro; Yar Johan (AGRITROPICA : Journal of Agricultural Sciences, 2023)
This Study aims to analyse developing a strategy for developing the tourist infrastructure on Tikus Island.  Information accessibility was determined to be the priority strategy that was urgently required based on the findings of the analysis performed using AHP.  This strategy aims to enhance travellers' overall travel experiences by encouraging them to make educated decisions.  Information on marine tourism is essential, especially on a small island like Tikus Island.  Second, the accessibility and condition of public restrooms for tourists.  Third, the significance of having appropriate transit vessels to accommodate maritime visitors.  Fourth, the strategy concentrates on offering suitable lodging choices and amenities for maritime tourists Fifth, it stresses the accessibility of dining establishments geared toward marine tourists.  Sixth, it focuses on giving visitors access to sufficient parking.  It seeks to address guests' parking requirements when they arrive in private vehicles by providing easy-to-access parking places close to popular tourist attractions.  Seventh, highlights the value of having efficient management processes to deal with potential risks and emergencies.  Supporting variables were found to have a tourism infrastructure development strategy on Tikus Island.  This research explains a lot about the new types of infrastructure that can be applied in the region.  The recommendations given have long-term development goals and strategic innovations.  The results of this study are beneficial as a reference for sustainable regional development that focuses on increasing the income of coastal communities.  Utilization of Tikus Island natural resources with good facilities.